(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The planned botanical nature reserve of local importance “Staroshvedskyi” is located in the area of the Zmiivka and Krasnyi Maiak village councils, Beryslav District, Kherson Province, Ukraine. It consists of two unplowed ravines (‘balkas’): Kostyrska and Shyroka and a 3.5 kilometers long Dnieper river terrace between them. The territory is characterized by a high differentiation of vegetation and habitats. As well as dominant steppe habitats, there are also meadows, shrublands, forest plantations, outcrops of limestone, loess and clay, cliffs, the Kakhovka Reservoir, and ruderal habitats. The planned reserve has a great conservation value. In this area, we identified 21 species of protected vascular plants, of which one species (Jurinea cyanoides) is included both in Resolution №4 of the Bern Convention, and the EU Habitats Directive. Ten plant species are included in the Red Data Book of Ukraine (Astragalus dasyanthus, A. ponticus, Elytrigia stipifolia, Ornithogalum boucheanum, Stipa capillata, S. lessingiana, S. pulcherrima, S. ucrainica, Tulipa biebersteiniana, T. gesneriana). Ten plant species are included in the Red List of Kherson Province (Amygdalus nana, Bellevalia sarmatica, Bromopsis heterophylla, Ephedra distachya, Hyacinthella leucophaea, Jurinea stoechadifolia, Poa sterilis, Quercus robur, Vinca herbacea, Vitis sylvestris). Furthemore, six rare communities from the planned reserve are included in the Green Data Book of Ukraine (Amygdaleta nanae, Elytrigieta stipifoliae, Stipeta capillatae, Stipeta lessingianae, Stipeta pulcherrimae, Stipeta ucrainicae). In view of the above, we propose to create a botanical reserve here for the preservation of important phytodiversity. Besides the important species here, the planned botanical nature reserve is important to habitats saving included to the Resolution №4 of the Bern Convention (E1.2. Perennial calcareous grassland and basic steppes and F3.247 Ponto-Sarmatic deciduous thickets).